Targeting strategies for improving the efficacy of nanomedicine in oncology - Villaverde, Gonzalo; Baeza, Alejandro (Beilstein Journal of Nanotechnology, 2019)
The use of nanoparticles as drug carriers has provided a powerful weapon in the fight against cancer. These nanocarriers are able to transport drugs that exhibit very different nature such as lipophilic or hydrophilic drugs and big macromolecules as proteins or RNA. Moreover, the external surface of these carriers can be decorated with different moieties with high affinity for specific membrane receptors of the tumoral cells to direct their action specifically to the malignant cells. The selectivity improvement yielded by these nanocarriers provided a significative enhancement in the efficacy of the transported drug, while the apparition of side effects in the host was reduced. Additionally, it is possible to incorporate targeting moieties selective for organelles of the cell, which improves even more the effect of the transported agents. In the last years, more sophisticated strategies such as the use of switchable, hierarchical or double targeting strategies have been proposed for overcoming some of the limitations of conventional targeting strategies. In this review, recent advances in the development of targeted nanoparticles will be described with the aim to present the current state of the art of this technology and its huge potential in the oncological field.
Keywords: antitumoral therapy; nanomedicine; smart nanocarriers; targeted nanoparticles